Seismic reflection profile AWI-20140280, Arctic Ocean - Estella Weigelt; Wolfram H Geissler (PANGAEA, 2023)
The data set provides unprocessed and processed seismic reflection data collected during Expedition PS87 (ARK-XXVIII/3) onboard RV Polarstern in the central and Arctic Ocean and Eurasia Basin in 2014. Detailed data acquisition parameters for the profile are documented in the expedition report (Stein, 2015). Metadata, recording parameters, and the seismic data processing sequence are documented in the EBCDIC-Headers enclosed in the seg-y files. Navigation information is included in the seg-y headers, and in the CDP-SHOT-latitude-longitude file (see data product). A ReadMe file additionally lists the metadata and recording parameters for the seismic profile. The data set is grouped into three categories: 1. Raw data comprise (a) demultiplexed seismic data in seg-y format, (b) a shot list of date, time and shot-number, and (c) navigation data with date, time, and coordinates. 2. Primary data consist of CDP-sorted data in seg-y format. 3. The data product is provided as (a) stacked or time-migrated version of the seismic profile in seg-y format and (b) a list with CDP and SHOT numbers as well as geographical coordinates. Please note that the low-frequency reflector that parallels the sea floor at depths of about 190 ms two-way travewltime (~150 m) is an artifact which has not been removed.